ChemInform Abstract: Inverse Electron Demand Diels—Alder (iEDDA)‐Initiated Conjugation: A (High) Potential Click Chemistry Scheme. Issue 36 (15th August 2013) - Knall, Astrid‐Caroline; Slugovc, Christian
Abstract Review: 49 refs.